Targeting C-reactive protein for the treatment of cardiovascular disease. - Pepys, M; Hirschfield, G; Tennent, G; Gallimore, JR; Kahan, M; Bellotti, V; Hawkins, P; Myers, R; Smith, M; Polara, A; Cobb, A; Ley, S; et al. (2006)
Complement-mediated inflammation exacerbates the tissue injury of ischaemic necrosis in heart attacks and strokes, the most common causes of death in developed countries. Large infarct size increases immediate morbidity and mortality and, in survivors of the acute event, larger non-functional scars adversely affect long-term prognosis. There is thus an important unmet medical need for new cardioprotective and neuroprotective treatments. We have previously shown that human C-reactive protein (CRP), the classical acute-phase protein that binds to ligands exposed in damaged tissue and then activates complement, increases myocardial and cerebral infarct size in rats subjected to coronary or cerebral artery ligation, respectively. Rat CRP does not activate rat complement, whereas human CRP activates both rat and human complement. Administration of human CRP to rats is thus an excellent model for the actions of endogenous human CRP. Here we report the design, synthesis and efficacy of 1,6-bis(phosphocholine)-hexane as a specific small-molecule inhibitor of CRP. Five molecules of this palindromic compound are bound by two pentameric CRP molecules, crosslinking and occluding the ligand-binding B-face of CRP and blocking its functions. Administration of 1,6-bis(phosphocholine)-hexane to rats undergoing acute myocardial infarction abrogated the increase in infarct size and cardiac dysfunction produced by injection of human CRP. Therapeutic inhibition of CRP is thus a promising new approach to cardioprotection in acute myocardial infarction, and may also provide neuroprotection in stroke. Potential wider applications include other inflammatory, infective and tissue-damaging conditions characterized by increased CRP production, in which binding of CRP to exposed ligands in damaged cells may lead to complement-mediated exacerbation of tissue injury.